The Effect of Corporate Governance on Tax Avoidance: Empirical Evidence of the Consumer Goods Industry Sector - Subhan Subhan; Leily Nur Indah Fitriana; Rohmaniyah Rohmaniyah (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
The aims of this reseach to determine the effect of institutional ownership, audit committee, audit quality, and independent board of commissioners on tax avoidance in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2017-2019. The method used in this research is quantitative. The sampling technique used random sampling method, based on the established criteria obtained a sample of 33 companies. The results of research on institutional ownership, audit committee, audit quality and independent board of commissioners have no partial effect on tax avoidance.